Interaction of Manganese(II) with Proton Pump Inhibitor at Different pH: A Cyclic Voltammetric Study (Dhaka University Journal of Science, 2016)
The electrochemistry of Mn2+ at different pH (3.5-4.5) in acetate buffer solution has been investigated, using cyclic voltammetric method at glassy carbon electrode (GCE). Cyclic voltammograms (CVs) of Mn2+ show two cathodic and an anodic peaks over the entire investigated pH. The CVs of Mn2+ has also been performed in presence of proton pump inhibitors (PPIs) such as omeprazole, pantoprazole, esomeprazole and rabeprazole to elucidate the interaction of Mn2+ with the PPIs in acetate buffer solution. At the studied pH, a reasonably strong interaction was observed between Mn2+ and PPIs at different molar ratio of Mn2+ ion and PPIs. However, maximum interaction has been found at 1:2 molar ratio of Mn2+ and PPIs. This indicates the most suitable condition for the interaction between Mn2+ and PPIs. These results could allow insight into the interactions of metal ions with the PPIs.Dhaka Univ. J. Sci. 64(2): 115-120, 2016 (July)